2001
DOI: 10.1128/jvi.75.15.7086-7096.2001
|View full text |Cite
|
Sign up to set email alerts
|

Wild Mandrillus sphinx Are Carriers of Two Types of Lentivirus

Abstract: Mandrillus sphinx, a large primate living in Cameroon and Gabon and belonging to the Papionini tribe, was reported to be infected by a simian immunodeficiency virus (SIV) (SIVmndGB1) as early as 1988. Here, we have identified a second, highly divergent SIVmnd (designated SIVmnd-2). Genomic organization differs between the two viral types; SIVmnd-2 has the additional vpx gene, like other SIVs naturally infecting the Papionini tribe (SIVsm and SIVrcm) and in contrast to the other SIVmnd type (here designated SIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
144
2
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(163 citation statements)
references
References 39 publications
13
144
2
2
Order By: Relevance
“…The first mosaic SIV was SIVagmSAB, isolated from a West African sabaeus monkey. Also, the recently described full-length genome sequences of SIVrcm from red-capped mangabeys in Nigeria, SIVmnd2 and SIVdrl from mandrills and drills, and SIVgsn from greater spot-nosed monkeys in Cameroon showed that these SIVs present discordant phylogenies, depending on the region of their genomes studied (4,8,14,27).…”
mentioning
confidence: 99%
“…The first mosaic SIV was SIVagmSAB, isolated from a West African sabaeus monkey. Also, the recently described full-length genome sequences of SIVrcm from red-capped mangabeys in Nigeria, SIVmnd2 and SIVdrl from mandrills and drills, and SIVgsn from greater spot-nosed monkeys in Cameroon showed that these SIVs present discordant phylogenies, depending on the region of their genomes studied (4,8,14,27).…”
mentioning
confidence: 99%
“…A substantial proportion of wild-living primates in Central Africa are naturally infected with Simian Immunodeficiency Viruses (SIVs) [161,162,163], Simian T-cell Lymphotropic Viruses (STLVs) [164,165,166,167], Simian Foamy Viruses (SFV) [168] and also Hepatitis B Viruses (HBV) [169].…”
Section: Pathogens In Non-human Primatesmentioning
confidence: 99%
“…SIVs are lentiviruses that are found naturally in a great variety of nonhuman primates from Equatorial Africa, including but no restricted to chimpanzees (SIVcpz), mandrills, (SIVmnd-1 and SIVmnd-2), drills (SIVdrl), talapoin monkeys (SIVtal), sun tailed monkeys (SIVsun), African green monkeys (SIVagm), red-capped mangabeys (SIVrcm) (see [162,163,170] and [171] for review). The evolutionary origins of these related viruses have been studied by amplification of the gag, pol, and env genes, and by construction and analysis of evolutionary trees.…”
Section: Pathogens In Non-human Primatesmentioning
confidence: 99%
“…En effet, certains de ces virus ne peuvent pas être classés parmi les six groupes précé-demment définis, car ils possèdent des génomes hybrides ou mosaïques, signes de recombinaison entre souches de différentes lignées ; c'est le cas, entre autres, du SIVmnd-2 des mandrills et du SIVgsn des singes hocheurs [4,5]. Pour expliquer ces données génétiques, deux modes principaux d'évolution, avec ou sans transfert interespèces, peuvent être proposés.…”
unclassified
“…Ils sont classés en six lignées phylogénétiques distinctes [3] (Figure 1); cependant, la caractérisation d'un nombre de plus en plus important de virus diffé-rents a souligné que les relations phylogénétiques entre ces lentivirus de primates ne peuvent être interprétées de manière simple. En effet, certains de ces virus ne peuvent pas être classés parmi les six groupes précé-demment définis, car ils possèdent des génomes hybrides ou mosaïques, signes de recombinaison entre souches de différentes lignées ; c'est le cas, entre autres, du SIVmnd-2 des mandrills et du SIVgsn des singes hocheurs [4,5]. Pour expliquer ces données génétiques, deux modes principaux d'évolution, avec ou sans transfert interespèces, peuvent être proposés.…”
unclassified